Impact of preventive detention on the Peruvian Criminal Justice System; Tacna, 2008 - 2013 - Chávez Torres, Wilber Alberto (2017)
This research was conducted in order to determine the impact of the application of preventive detention in the efficiency of the Peruvian criminal justice system in the judicial district of Tacna, 2008-2013. The research work corresponds to a basic type. Also, the study is not experimental cross-sectional descriptive relational level. For this purpose the information obtained through the implementation of the Observation Form, and the Certificate of Interview was considered; as instruments for measuring the variables studied. The data were tabulated and analyzed by tables and figures. Once the phase of analysis and interpretation of the results indicated that a) the application of preventive detention, would have favorable relationship with the principle of immediacy, in proceedings in the judicial district of Tacna with the implementation of the new Code criminal; and, b) the application of preventive detention would impact significantly on the protection of fundamental rights in the proceedings in the judicial district of Tacna.